CASTILLO, R. (2020). Filósofos de paseo. Madrid: Turner. - Argüelles Rozada, Isabel (Daimon Revista Internacional de Filosofia, 2023)
Reseña de CASTILLO, R. (2020). Filósofos de paseo. Madrid: Turner.